Digital Leadership and Digital Competence in Enhancing Government Service Effectiveness: The Moderating Role of Organizational Structure in Ciasem District, Subang - Amri, Kaka Mutiul; Fadli, Uus MD; Rosmawati, Ery (Research in Management of Technology and Business, 2026)
This study aims to analyze the influence of digital leadership and digital competence on the effectiveness of government apparatus services with organizational structure as a moderating variable in Ciasem Subdistrict, Subang Regency. The study uses a quantitative approach with a survey method. The research population consisted of 106 subdistrict and village government officials, with a sample of 97 respondents determined using the Slovin formula and proportioned stratified random sampling technique. Data were collected through questionnaires and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with the help of SmartPLS 4.0. The results show that digital leadership and digital competence have a positive and significant effect on service effectiveness. However, organizational structure was not found to moderate the effect of digital leadership or digital competence on service effectiveness. These findings indicate that improvements in public service effectiveness are more directly influenced by the digital leadership and digital competence of officials. This study contributes theoretically to the study of digital transformation-based public management and has practical implications for improving the quality of public services at the subdistrict level.